2018
DOI: 10.1108/sgpe-d-17-00046
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral student mentorship in social work education: a Canadian example

Abstract: Purpose This paper aims to present a thematic analysis investigating the experiences and reflections of doctoral students in social work at a Canadian university who were mentored in the development of teaching expertise, including course design, delivery and evaluation, by a senior faculty member. Recommendations to others who are considering engaging in doctoral student teaching mentorship are presented. Design/methodology/approach The paper examines the authors’ reflections on their experiences of doctora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Current sources of support such as supervisory relationships, program models, writing groups and peer mentoring have the potential to make a positive impact on program completion, but may lack depth and miss the opportunity to leverage self-regulation. Doctoral students can learn from high-quality supervisory relationships that provide support and impact their professional identity (Fulton et al , 2018; Lechuga, 2011). Supportive supervisory relationships may result in a significant reduction in emotional exhaustion, impression management and facades of conformity (Devine and Hunter, 2016).…”
Section: Grounding In the Theory And Literaturementioning
confidence: 99%
“…Current sources of support such as supervisory relationships, program models, writing groups and peer mentoring have the potential to make a positive impact on program completion, but may lack depth and miss the opportunity to leverage self-regulation. Doctoral students can learn from high-quality supervisory relationships that provide support and impact their professional identity (Fulton et al , 2018; Lechuga, 2011). Supportive supervisory relationships may result in a significant reduction in emotional exhaustion, impression management and facades of conformity (Devine and Hunter, 2016).…”
Section: Grounding In the Theory And Literaturementioning
confidence: 99%
“…Several strategies have been proposed to address this challenge by scholars who have evaluated teaching of research skills in undergraduate and graduate social work programs. For example, Horowitz and Christopher (2013) recommended enlisting doctoral students as mentors for undergraduate students, suggesting that doctoral students benefit as mentors by preparing for supervisory and teaching aspects of future roles and undergraduate students benefit from the opportunity to work with emerging scholars who are willing to share their knowledge and enthusiasm (Fulton, Walsh, Gulbrandsen, Tong, & Azulai, 2018). Similarly, Aponte et al (2015) highlighted the potential for peer mentoring to foster learning in research learning programs and suggested that "social interaction and collaboration among peers contributes to better outcomes than learning independently" (p. 323).…”
Section: Additional Observationsmentioning
confidence: 99%